Causal relationship of genetically predicted circulating micronutrients levels with the risk of kidney stone disease: a Mendelian randomization study - Yang, Junyi; Wu, Weisong; Amier, Yirixiatijiang; Li, Xianmiao; Wan, Wenlong; Yu, Xiao (Frontiers in Nutrition, 2023)
Background: Current studies have reported conflicting associations between circulating micronutrient levels and kidney stone disease (KSD). We aimed to elucidate the causal relationship between circulating micronutrient levels and KSD by a two-sample Mendelian randomization (MR) analysis. Methods: 36 single nucleotide polymorphisms (SNPs) from published genome-wide association studies (GWAS) significantly associated with eight micronutrients (vitamin B12, folic acid, magnesium, iron, phosphorus, copper, zinc, and selenium) were used as instrumental variables. The GWAS summary data associated with KSD (8060 cases and 301,094 controls) were obtained from the FinnGen consortium. Inverse variance weighted was the main MR analysis method. MR-Pleiotropy RESidual Sum and Outlier (MR-PRESSO), weighted median and MR-Egger were used to assess pleiotropy and heterogeneity. Results: Genetically predicted circulating vitamin B12 and zinc levels were causally associated with the risk of KSD (vitamin B12: OR: 1.17, 95% CI: 1.04–1.32, p = 0.008; zinc: OR: 1.15, 95% CI: 1.03–1.28, p = 0.015). We found no evidence that other circulating micronutrients were associated with risk of KSD. P-value for Cochrane Q test, MR Egger intercept test, and MR-PRESSO were > 0.05, indicating no significant heterogeneity or horizontal pleiotropy in this MR analysis. Conclusions: Increasing circulating zinc levels may increase the risk of KSD. More studies are needed to provide evidence on whether genetically predicted circulating vitamin B12 and zinc levels are a risk factor for KSD.